The effect of financial pressure and corporate social responsibility on tax aggressiveness: The moderating effect of the audit committee - Devi Safitri; Zirman Zirman; Supriono Supriono (The Indonesian Accounting Review, 2024)
This research aims to examine the effect of financial pressure and corporate social responsibility (CSR) on tax aggressiveness. In addition, this research also investigates whether audit committee can moderate the effect of financial pressure and CSR on tax aggressiveness. In this research, the financial pressures include financial targets and external pressures. This quantitative research uses secondary data with the population of all manufacturing companies listed on the Indonesian Stock Exchange period 2019-2021. Sampling is conducted using purposive sampling technique involving 216 companies obtained during three years of observation. Data analysis is conducted using Smart PLS 3.0 with SEM-PLS application to test the direct and moderating effect. The results of this research show that financial target has a negative effect on tax aggressiveness, while external pressure has a positive effect on tax aggressiveness. CSR has no effect on tax aggressiveness. Audit committee cannot moderate the effect of financial target, external pressure, and CSR on tax aggressiveness. This research contributes to the development of accounting literacy, especially in the study of financial pressure, CSR, audit committee and tax aggressiveness. Measuring tax aggressiveness can be done using CETR by adding the CSR variable as an independent variable with GRI standards. In addition, this research also uses financial pressure variable from the fraud triangle theory which is related to tax aggressiveness.